CT evaluation of malignant PNS mass and histopathological correlation (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Computed tomography (CT) is the gold standard for exact delineation of paranasal sinus(PNS) disease. There are many radiologically important diseases of paranasal sinuses. Objective: to evaluate the malignant PNS mass by computed tomographic image and the findings of this modality were compared with histopathological result.Methods: It was a cross sectional type of study and carried out with suspected PNS mass having patients during January 2009 to October 2010.Results: The mean age of the patients was 35.95 ± 18.24 and common complaints of the patients were nasal obstruction (73.7%) and maximum 53.9% patients had PNS mass in maxillary sinuses. Out of 76 cases 21.1 % found malignant mass on CT and after histopathology 19. 7% had malignant mass. Out of all cases 14 were diagnosed as malignant PNS mass by CT scan and confirmed by histopathological evaluation and they were true positive. Two cases were diagnosed as malignant PNS mass by CT scan but not confirmed by histopathological findings and they were false positive. Of 60 cases, which were diagnosed by CT scan, one was confirmed as malignant and 59 were benign by histopathology. They were false negative and true negative respectively. Sensitivity of CT scan to diagnose malignant PNS mass was 93.3%, specificity 96.7%, positive predictive value 87.5%, negative predictive value 98.3% and accuracy 96.1 %. Conclusion: CT scan of the malignant para nasal sinus mass provides more information and better image quality and CT diagnosis correlate well with the findings of histopathology.